SAT0212 Pericardial Effusion Related To Systemic Sclerosis: A Possible Contribution of The Serum Levels of Adipokines and Interleukines. (15th July 2016) - Chialà, A.; Rotondo, C.; Anelli, M.G.; Scioscia, C.; Praino, E.; Perniola, S.; Nivuori, M.; Natuzzi, D.; Fiorentini, C.; Lopalco, G.; Lapadula, G.; Iannone, F.
Abstract : Background: Pericardial effusion (PE) is a common clinical manifestation in systemic sclerosis (SSc). Few data are available about its pathogenesis. The role of adipokines and interleukins produced by the adipose tissue and the immune system in PE related to SSc had never been investigated. Objectives: This study aimed at evaluating the differences in serum levels of adipokines and interleukins (IL) in systemic sclerosis (SSc) patients with and without PE. Methods: A total of 87 outpatients (84 female, mean age of 52, 6±14, 2 ys, and disease duration of 8, 2±6, 7 ys), who fulfilled the ACR/EULAR 2013 SSc classification criteria, were recruited in this study. The anthropometric measures, as body mass index (BMI), demographic, clinical and laboratoristic characteristics and SSc related manifestations were assessed in each patient. The presence of PE was evaluated by means of echocardiographic techniques (the presence of fluid ≥5 cc was considered pathologic). Sera levels of adiponectin, leptin, resistin, visfatin, tumor necrosis factor α (TNF-α), interferon g (INF-g), IL-2, IL-10 and IL-17 were measured in SSc patients, using Multiplex Immunoassay (Bioplex 200 System), by means of two kits (Bioplex ProTM Cytokine/Chemokine and Growth Factor Assay e Bioplex Pro Diabetes Assay). The data normality was verified using Kolmogorov-Smirnov Test; the comparisons between SSc patients groups were evaluated by Mann-Whitney U test and t-student test, where appropiate. Statistic significance was set at p≤0, 05. The results are expressed as median and interquartile range (IQR) or means±1standard deviation. The data analysis were assessed using IBM SPSS statistic 20. Results: 11 SSc patients had PE. The SSc patients groups (with and without PE) did not differ in age, sex and BMI. 11 SSc patients were obese (BMI≥30) (2 with PE and 9 without PE). We found significant differences between SSc patients with PE and without PE in sera levels of visfatin (1546, 9 (8590, 9) vs 388, 8 (103); p=0, 036), adiponectin (2845000 (4132900, 0) vs 5272100, 0 (8243600, 0); p=0, 027) and IL-17 (1, 33 (3, 5) vs 0, 05 (0, 56); p=0, 45). Moreover higher adiponectin/leptin ratio was found in patients with PE than SSc patients without PE (569, 2 (1415, 3) vs 166, 9 (504, 9) p=0, 032). The presence of interstitial lung disease, pulmonary arterial hypertension, limited or diffuse skin subset, the different nail fold videocapillaroscopy pattern and the modified Rodnan skin score did not influenced the serum levels of adipokines and IL. In the SSc patients with PE there is no differences in visfatin and adiponectin serum level and adiponectine/leptin ratio between patients that are in menopause and those who are not. Conclusions: The visfatin and adiponectin could play an important role in pathogetic mechanism in pericardial effusion related to SSc. Further study are necessary to unravel a role of visfatin and adiponectin as biomarkers of SSc and a role of the adipose tissue and innate immune system in PE related to SSc pathology. Disclosure of Interest: None declared